Undergraduate students’ expectations of practical work in university physics - Dunnett, Kirsty (Högre utbildning, 2024)
Instructors’ assumptions about students’ expectations can affect the opportunities and support they provide. A survey of students starting undergraduate degrees in physics in the UK and Sweden found that they expect that their laboratory work will contribute to skills acquisition, but also be difficult. Differences between institutions may reflect course structure or prior experience: for example, Swedish students have lower expectations of difficulty than UK students. Specific concerns around insufficient working equipment are more common in the UK, but Swedish students expect more explicit connections to theoretical courses. The implications for student motivation are discussed in relation to self-efficacy and expectancyvalue theory. Concern around practical work may have been obscured in earlier studies on students’ attitudes towards practical work and demonstrates the importance of including the student perspective in course design and delivery.